Autonomic Nervous System Team-Based Learning Module - Sarah Lerchenfeldt; Thomas Ferrari; Rodney Nyland; Gustavo Patino (Association of American Medical Colleges, 2016)
Abstract Introduction The team-based learning (TBL) instructional strategy promotes learning and retention, enhances student engagement, allows for a deeper understanding of foundational and applied concepts, and helps students' develop lifelong learning skills. The autonomic nervous system (ANS) TBL was created for first-year medical students in the Neuroscience 1 course at Oakland University William Beaumont School of Medicine. Methods The module covered the pathophysiology of ANS-related diseases and therapeutic agents that impact ANS function. By the conclusion of the module, students were able to diagnose different disease processes of the ANS, identify potential complications, and formulate appropriate management strategies. Four faculty members used backward design to create the ANS TBL. The preparatory assignment included reviewing content from previous didactic lectures and consolidating key information in provided tables. Key concepts were evaluated with readiness assurance tests. All application exercises adhered to the 4 S's. Results Over the course of 2 years, the class averages for the individual readiness assurance test were 79.8% and 87.6%. The class averages for the team readiness assurance test and application exercises were similar across both years. Course evaluations revealed that students found the TBL relevant and valuable. Discussion Similar TBL modules available on MedEdPORTAL are not integrated to include different aspects of the basic and clinical sciences. This ANS TBL was used to help students integrate several essential concepts, including neuroanatomy, neurophysiology, neuropharmacology, and clinical neurology. Students were very enthusiastic and engaged throughout the ANS TBL as it contained relevant case-based scenarios with questions that were meaningful for clinical practice.